Keagungan Islam; Komparasi Politik, Ekonomi, Keagamaan Antara Akbar Agung dan Sultan Agung - Yuana Tri Utomo (At-Tauzi : Jurnal Ekonomi Islam, 2021)
Writing the greatness of Islamic civilization history has been presented by many intellectuals. However, many pearls of civilization are still buried inviting the next researchers to dig it back. Study of Islamic civilization history requires precision because of different perspectives due to various interpretations of historical facts. This paper describes two muslims figure in their respective periods and territories, Akbar Agung (1542-1605 M) in Hindia and Sultan Agung (1593-1645 M) in Nusantara. This paper uses a phenomenological descriptive by comparing three variables: political, economic, and religious. Intake of data through literature studies from libraries, collection books, and interviews with cultural figures. The data is analyzed by triangulations. The results reveal that phenomenon of Akbar and Sultan Agung in field of politics, economic and religious still felt today. The prominent political field of Akbar is an Indian territory that stretches with interfaith unity, while Sultan Agung becomes national hero of Indonesia for his services against the colonization. The prominent economic field for Akbar is prohibition of taxes for non-Muslims, while Sultan Agung is the VOC's debt to oppose the VOC. The prominent religious field for Akbar is teachings of divine and for Sultan Agung is unifying of Javanese calendar and Islam.